2016
DOI: 10.1161/atvbaha.115.307085
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Activate a CD36-Dependent Signaling Pathway to Inhibit Microvascular Endothelial Cell Migration and Tube Formation

Abstract: Objective Literature on the effect of cell-derived extracellular vesicles (EV), ≤1μm vesicles shed from various cell types during activation or apoptosis, on microvascular endothelial cell (MVEC) signaling is conflicting. Thrombospondin-1 and related proteins induce anti-angiogenic signals in MVEC via CD36. CD36 binds EV via phosphatidylserine (PS) exposed on their surface but the effects of this interaction on MVEC functions are not known. We hypothesized that EV would inhibit angiogenic MVEC functions via CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 46 publications
1
41
0
1
Order By: Relevance
“…At present, less than a handful of studies have been published on the effect of monocyte Exos on target cells. In most of these studies, extracellular vesicles, including microparticles, from THP1 acute monocytic leukemia cells were used (26)(27)(28)(29). Microparticles are distinct from Exos, in that they are larger and originate from a different cellular compartment.…”
Section: Discussionmentioning
confidence: 99%
“…At present, less than a handful of studies have been published on the effect of monocyte Exos on target cells. In most of these studies, extracellular vesicles, including microparticles, from THP1 acute monocytic leukemia cells were used (26)(27)(28)(29). Microparticles are distinct from Exos, in that they are larger and originate from a different cellular compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that exosomal miRNA can modulate angiogenesis through targeting different mRNAs (van Balkom et al, ; Kang et al, ; Liang et al, ; Ramakrishnan et al, ). Exosomal miR‐126‐3p from CD34 + stem cells (Mathiyalagan et al, ), exosomal miR‐125a from adipose‐derived MSCs (Liang et al, ), exosomal miR‐23a from hypoxic lung cells (Hsu et al, ), exosomal miR‐17‐92 cluster and miR‐21 from leukaemia cells (Umezu et al, ), and exosomal miR‐21 from glioma stem cell (Sun et al, ) promote endothelial cell viability, proliferation, migration, or tube formation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Ramakrishnan et al reported that EV isolated from various sources in vitro , including endothelial cells, circulating red blood cells and tumor cells, as well as circulating EV isolated from healthy humans and subjects with vasculitis, inhibited microvascular endothelial cell migration and tube‐like structure formation. They further demonstrated that EV from different sources inhibited the endothelial cell pro‐angiogenic activity due to the interaction of PS on EV membranes with CD36 on microvascular endothelial cells, involving NADPH and Fyn kinase–mediated ROS generation . In a more recent study, the angiogenic effect of exosomes derived from two oral squamous cell carcinoma cell lines (SCC15 and HSC3) was found to increase HUVEC migration and tube formation .…”
Section: Effects Of Ev On Endothelial Cellsmentioning
confidence: 92%
“…69 Kucharzewska and colleagues reported that hypoxic exosomes ac- to the interaction of PS on EV membranes with CD36 on microvascular endothelial cells, involving NADPH and Fyn kinase-mediated ROS generation. 72 In a more recent study, the angiogenic effect of exosomes derived from two oral squamous cell carcinoma cell lines (SCC15 and HSC3) was found to increase HUVEC migration and tube formation. 73 Thus, many different EV proteins, including but not limited to CD97, 74 the heparin-binding factor midkine, 75 and annexin II, 76 have been shown to support angiogenesis in cancer models by affecting different mechanisms.…”
Section: Ev On Tumor Microvesselsmentioning
confidence: 95%